Lunchtime on the go: Understanding street food consumption habits of office workers in cities in Vietnam - Phuong, Nguyen Van; Truc, Tran Thi; Quang, Hoang Ngoc; Quynh, Pham Ngoc Huong (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the factors influencing street food consumption habits by analyzing the data collected from 572 office workers in the inner districts of Hanoi, Da Nang, and Ho Chi Minh City using Partial Least Squares Structural Equation Modeling (PLS-SEM) and the Theory of Planned Behavior (TPB). The analysis emphasizes the significant roles of convenience, peer influence, food quality, and health perceptions in shaping consumer behavior. Convenience and accessibility, along with social recommendations, are identified as strong determinants, while food quality and health perceptions reflect consumers’ concerns about sensory attributes and health implications. Although personal eating habits have a less pronounced impact, they still contribute to consumption patterns. The findings suggest several implications for policymakers and businesses. Policymakers should focus on enhancing the availability and safety of street food, including streamlining vendor permits and improving infrastructure. Public health initiatives should educate consumers about health risks and promote healthier options. For businesses, leveraging social influence through targeted marketing and investing in food quality and health benefits can enhance consumer engagement and market appeal. However, the study’s focus on a specific demographic may limit the generalizability of the findings. Further research across diverse populations is recommended to validate these insights.